Room-Temperature Superplasticity in an Ultrafine-Grained Magnesium Alloy - Edalati, Kaveh (Sci Rep, 2017)
Superplasticity, a phenomenon of high tensile elongation in polycrystalline materials, is highly effective in fabrication of complex parts by metal forming without any machining. Superplasticity typically occurs only at elevated homologous temperatures, where thermally-activated deformation mechanisms dominate. Here, we report the first observation of room-temperature superplasticity in a magnesium alloy, which challenges the commonly-held view of the poor room-temperature plasticity of magnesium alloys. An ultrafine-grained magnesium-lithium (Mg-8 wt.%Li) alloy produced by severe plastic deformation demonstrated 440% elongation at room temperature (0.35 T (m)) with a strain-rate sensitivity of 0.37. These unique properties were associated with enhanced grain-boundary sliding, which was approximately 60% of the total elongation. This enhancement originates from fast grain-boundary diffusion caused by the Li segregation along the grain boundaries and the formation of Li-rich interphases. This discovery introduces a new approach for controlling the room-temperature superplasticity by engineering grain-boundary composition and diffusion, which is of importance in metal forming technology without heating.